Kesetaraan Gender Dalam Pembelajaran di Madrasah Ibtidaiyah Nusantara - Muslihati Muslihati (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2008)
A qualitative research with case-study design was conducted to explore the implementing of gender equality by the teachers in learning process for 4th to 6th graders at Islamic elementary school. Interviews and observations were administered as tools for data collection. The principal, the teachers and the students were then interviewed and the school environment was observed.Using qualitative coding and the Gender Analysis Pathway (GAP) method to analyze the implementation of gender equality in learning process Indicate the moderate level of gender equality for the teachers.Regardless of their perspectives in seeing boys and girls have the same level of competitiveness as well as the opportunities for success, they treat them differently when assigning tasks in which physical strength are needed to perform such tasks. They assign the girls with the tasks that no need too much physical strength as the controversies for the boys.